Proses Berpikir Ilmiah Siswa Tipe Climber Dalam Pemecahan Masalah Biologi Di SMA: Scientific Thinking Process of Students Type Climber In Problem Solving of Biology at Junior High School - Pebriana Pebriana; Kamid Kamid; Bambang Hariyadi (Universitas Jambi, 2019)
The process of scientific thinking and the level of intelligence AQ (Adversity Quotient) has an essential role in solving various biological problems. This study aims to determine the type of scientific thinking process of a climber student in problem-solving in biology. The subject of this research was a climber type student, obtained through the ARP test. The results of this study indicate that the subject can perform scientific thinking in solving biological problems. He employed four stages according to Polya problem solving including (1) understanding the problem, ranging from making inquiries about the object of empirical and limitations to identify the factors involved; (2) planning problem-solving, begins with formulating a framework to reason, then makes arguments that explain the relationship between the various factors interrelated, (3) implementing a problem-solving plan, which at this stage the subject measures as well as determines the planning phase of problem-solving, and (4) evaluating the results of problem-solving, starting to explain the reasons choosing an answer from the problem, summed up the results of problem-solving and reflect the success of problem-solving.